INVESTIGATING CONDITIONS ENSURING RELIABILITY OF THE PRIORITY VECTORS - Cavallo, Bice; D’Apuzzo, Livia; Basile, Luciano (BDC. Bollettino Del Centro Calza Bini, 2014)
In this paper, we investigate conditions, weaker than consistency, that a pairwise comparison matrix has to satisfy in order to ensure that priority vectors proposed in literature are ordinal evaluation vectors for the actual ranking. In particular, we introduce a partial order on the rows of a pairwise comparison matrix; if it is a simple order, then the matrix is transitive, the actual ranking is easily established and priority vectors are ordinal evaluation vectors for the actual ranking. Keywords: pairwise comparison matrices, ordinal evaluation vectors, simple order